2020
DOI: 10.5937/fmet2001090h
|View full text |Cite
|
Sign up to set email alerts
|

One-at-a-time sensitivity study of a nonlinear fire truck suspension model

Abstract: In this paper the detailed OAT (one-at-a-time) sensitivity analysis of a nonlinear fire truck suspension system is carried out with numerical simulation. As output to measure sensitivity the RMS of acceleration was chosen, which can be calculated with numerical simulations easily. The degree of sensitivity was measured with a sensitivity index and based on it sensitivity Fuzzy-sets were established. The membership of each parameter to the Fuzzy sets is calculated and based on it, it was determined which parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The detailed sensitivity study of 21 different parameters of a fire truck suspension system using the half car model with nonlinear characteristics using the RMS of acceleration has been already accomplished [29]. It was observed that the nonlinear coefficient of the rear spring is the most sensitive parameter.…”
Section: Table VImentioning
confidence: 99%
“…The detailed sensitivity study of 21 different parameters of a fire truck suspension system using the half car model with nonlinear characteristics using the RMS of acceleration has been already accomplished [29]. It was observed that the nonlinear coefficient of the rear spring is the most sensitive parameter.…”
Section: Table VImentioning
confidence: 99%